First-principles study of hydrogen capacity in Li2TiO3 crystal - Li, Yan-Wei; Zhang, Yong-Shuai; Meng, Shuai; Yang, Wen; Li, Kun (International journal of modern physics. C, Computational physics, physical computation, 2024)
Understanding the hydrogen (H) capacity, which represents the tritium capacity in Li2TiO3 crystal has become an important aspect of the tritium release process of nuclear fusion. In this work, a systematic density-functional-theory (DFT) study is performed to investigate the trapping and accumulation of H in Li2TiO3 crystal. In perfect crystal, the H adsorption properties are investigated and the maximum number of trapped H atoms are obtained. In the defect models, by calculating the trapping energy and Bader charge, we find that a Li vacancy can capture four H atoms while the capacity of a Ti vacancy is seven and then other H atoms tend to be trapped by interstitial sites outside the vacancy. Then the H capacity both inside and outside the vacancy in the defect models is studied and analyzed. According to our calculations, crystals containing a vacancy present stronger H trapping abilities than perfect crystals, especially for the crystal with a Ti vacancy. In addition, the increase of H atoms in the vacancy facilitates the formation of the neighboring vacancy so that more H atoms can be accommodated in the crystal with vacancy. Our results reveal the H capacity of different Li2TiO3 models, which provide theoretical support for related tritium release experiments.